Het verlangen geschilderd en verwoord. Over het gebruik van moderne kunstwerken in de eredienst - Ploeger, Albert K. (Jaarboek voor liturgieonderzoek, 1996)
The central question in this article is: What function can a modern object of art have for the interpretation of Scripture within worship? First we consider in which ways church attendants appreciate a service (§ 1). Secondly we discuss the meaning and purpose of a service, which must be found in Christian spirituality (§ 2). In discussion with Steensma, who investigated the use of modern paintings in worship, we develop criteria for the most efficient use of paintings in worship (§ 3). The question about Christian spirituality is taken up: It is seen as the desire for the righteous and good life of mankind in the presence of the Eternal. This longing we can share together, but it always remains a mystery. This mystery is the background of biblical narrative, and can be found too in objects of modern art. We therefore discuss what kind of support objects of art can give to interpret Gods Word, in order to experience the mystery. But the paradox between mystery and interpretation is also stressed (§ 4). The outcome leads us to some consequences for the use of objects of art (§§ 5 and 6).